PERKAWINAN DALAM LANDSCAP KEINDONESIAAN (PENDEKATAN ANTROPOLOGI, SOSIOLOGI, HUKUM) - Soeprijanto, Troeboes (FPIPSKR Universitas PGRI Semarang, 2024)
The development of human civilization/growth and development, humans, Koentjaraningrat, in his introduction to anthropology, published by Rineka Cipta, eighth edition, last published in 1981, explains that